The Development of Thematic Praxis Module in Children's Literature Pantun learning Based on Nationalism Character in Elementary School - Heryanto, Dwi; Murron, Faisal Sadam; Rahmawati, Evi; Cahya Anasta, Non Dwishiera; Magistra, Ari Arasy (Widyagogik, 2023)
Efforts to reconstruct the cultivation of character values, one of which is the character of nationalism through the development of the thematic module of children's literature in poetry learning, are due to the emergence of the phenomenon of the disappearance of national identity with the loss of character values in social life in society. This study uses a qualitative method with a Design and Development (DD) model, which refers to the PPE model modified by Richey and Klein. The process of developing this module uses planning, production, and evaluation steps through a one-time validation and improvement process to improve the quality of the final design. The results of the module development in rhyme learning based on the assessment of experts and validation show that it is feasible to use with an average overall score of 96.14% in the "Very Good" category. It can be concluded that this research is expected to be able to become a constructive reference in rhyme learning by inculcating meaningful nationalism character values through the developed modules.